In Situ Binder-Free and Hydrothermal Growth of Nanostructured NiCo2S4/Ni Electrodes for Solid-State Hybrid Supercapacitors - M. Mohamed Ismail (MDPI AG, 2021)
Herein, we report a comparison of the electrochemical performance of two kinds of NiCo2S4-based electrodes for solid-state hybrid supercapacitors (HSCs). For the binder-free electrode, NiCo2S4 was grown on Ni foam by the chemical bath deposition (CBD) method. For the binder-using electrode, NiCo2S4 powder was synthesized by the hydrothermal method. FESEM images depicted the hierarchical nanostructure of NiCo2S4 synthesized by the hydrothermal method and uniform distribution of nanostructured NiCo2S4 grown on Ni foam by the CBD method. Half-cell studies of both NiCo2S4 electrodes showed them exhibiting battery-type charge storage behavior. To assemble HSCs, NiCo2S4 and activated carbon were used as a positive and negative electrode, respectively. Electrochemical studies of the HSCs showed that the accessible potential window was wide, up to 2.6 V, through cyclic voltammetry (CV) analysis. Chronopotentiometry (CP) studies revealed that the energy and power densities of binder-using HSC were 51.24 Wh/kg and 13 kW/kg at 1 Ag−1, respectively, which were relatively higher than those of the binder-free HSC. The binder-free HSC showed 52% cyclic stability, relatively higher than that of the binder-using HSC. Both HSCs, with unique benefits and burdens on energy storage performance, are discussed in this work.